The Synergistic Action of Electro-Fenton and White-Rot Fungi in the Degradation of Lignin - Hou, Lipeng; Ji, Dandan; Dong, Weifang; Yuan, Lin; Zhang, Fengshan; Li, Yan; Zang, Lihua (Frontiers in Bioengineering and Biotechnology, 2020)
White rot fungus are common lignin-degrading fungus. However, compared with microorganisms that biodegrade lignin alone, synergistic systems of Electro-Fenton procecesses and white rot fungi are superior because of their high efficiency, mild conditions and environmental friendliness. To investigate the details of lignin degradation by a synergistic system comprising Electro-Fenton processes and white rot fungi, lignin degradation was studied at different voltages with three lignin-degrading fungi (Phanerochaete chrysosporium, Lentinula edodes and Trametes versicolor). The lignin degradation efficiency (82 ~89 %) of the synergistic systems at 4 V was higher than that of a control at 96 h post inoculation. Furthermore, the H2O2 produced and phenolic lignin converted in the system can significantly enhance the efficiency of ligninolytic enzymes so that considerably increased enzyme activity was obtained by the synergistic action of Electro-Fenton processes and white rot fungi. 13C NMR spectroscopy revealed that aromatic structure units (103-162 ppm) were effectively degraded by three fungi. The study shows that the combination of Electro-Fenton processes and white-rot fungi treatment significantly improved the lignin degradation efficiency, which established a promising strategy for lignin degradation and valorization.